2013
DOI: 10.3791/50436
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of a Kv Channel into Lipid Membranes for Structural and Functional Studies

Abstract: To study the lipid-protein interaction in a reductionistic fashion, it is necessary to incorporate the membrane proteins into membranes of welldefined lipid composition. We are studying the lipid-dependent gating effects in a prototype voltage-gated potassium (Kv) channel, and have worked out detailed procedures to reconstitute the channels into different membrane systems. Our reconstitution procedures take consideration of both detergent-induced fusion of vesicles and the fusion of protein/detergent micelles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Following expression and purification (Fig. S2A), the protein was reconstituted into liposomes containing a 3:1 mixture of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE):1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (POPG) and applied to planar lipid bilayers of the same lipid composition for electrophysiological analysis following procedures established for other ion channels (21,22). Macroscopic currents recorded from bilayers containing BEST1 in the presence of ∼300 nM free Ca 2+ are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following expression and purification (Fig. S2A), the protein was reconstituted into liposomes containing a 3:1 mixture of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE):1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (POPG) and applied to planar lipid bilayers of the same lipid composition for electrophysiological analysis following procedures established for other ion channels (21,22). Macroscopic currents recorded from bilayers containing BEST1 in the presence of ∼300 nM free Ca 2+ are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Frozen liposomes were thawed and sonicated for approximately 10 s using an Ultrasonic Cleaner (Laboratory Supplies Company). All data are from recordings made using components analogous to the Warner planar lipid bilayer workstation (Warner Instruments) (21,22 ], ∼300 nM, as determined using Fura-2). Chlorided silver (Ag/AgCl) wires were used as electrodes, submerged in 3 M KCl, and connected to the bath solutions via agar-KCl salt bridges [2% (wt/vol) agar, 3 M KCl].…”
Section: Methodsmentioning
confidence: 99%
“…2C). We first tested if CHGB is a channel by bilayer recordings (Lee et al, 2013). The membrane-remodeling property made it difficult to record from many CHGB molecules.…”
Section: Introductionmentioning
confidence: 99%
“…During membrane reconstitution, many factors, including temperature, rate of detergent removal, ionic strength, pH, etc., may affect bilayer formation (Lee et al, 2013). Our stepwise removal of detergents may control the fusion of small membrane patches around proteins, as well as, in the later phase, the fusion of small vesicles in the solution into the bilayers around the proteins.…”
Section: Bsums Of Varying Dimensions and Lipid Compositionsmentioning
confidence: 99%
“…Similarly, we experienced difficulty in introducing sphingolipids into solvent-based BLMs and found that 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) or 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) in decane forms a sticky gel-like phase over time, probably caused by trace amounts of water. Additionally, the solvent-based BLMs have a significant amount of solvent (decane or squalene, for example), which may alter the physicochemical properties of the bilayers, especially phase separation, interactions between neutral lipids (such as cholesterol), and the islands of solvent molecules in membranes composed of composite lipids (Needham et al, 1988;Lee et al, 2013). To overcome many of these technical limitations, we developed a chemical procedure to generate a new bead-supported unilamellar membrane (bSUM) system.…”
mentioning
confidence: 99%